Video-assisted thoracoscopic diagnosis of trapped lung in malignant pleural effusions - P. Bonev; Iv. Novakov; I. Dimitrov; M. Vazheva; A. Uchikov (Trakia Journal of Sciences)
PURPOSE. The aim of this study is to present the role of video-assisted thoracoscopy to assess the ability of the lung to expand in malignant pleural effusions. METHODS. The survey was conducted for a 3-year period in 13 patients with histologically diagnosed malignant pleural effusion and trapped lung. In each of the patients video-assisted thoracoscopy was performed. RESULTS. Two reasons for trapped lung were identified. In 10 of the patients it was due to multiple metastatic nodules. In 3 cases the cause was a diffuse fibrotic involvement of the lung resulting from the metastatic process.CONCLUSIONS. Our research confirmed two causes of trapped lung in malignant pleural effusions: multiple metastases on the lung surface and diffuse lung fibrosis, induced by the metastatic process, with the increased role of multiple metastases on the lung surface.